STRATEGI KOMUNIKASI PEMASARAN POLITIK PADA PEMILU LEGISLATIF - Primus Adeodatur Latu Batara; Guntur Freddy Prisanto; Niken Febrina Ernungtyas; Irwansyah Irwansyah; Safira Hasna (Universitas Lambung Mangkurat, 2020)
The large number of parties in the 2019 legislative elections made political parties have to compete for political power in their constituencies. Political marketing communication strategies are needed to get the most votes and win in the democratic event every 5 years in Indonesia. East Nusa Tenggara I became one of the electoral districts that experienced fierce competition among the political parties, due to the large number of elite legislative members and political activists in this area. However, Nasdem as a new party was able to gain the most votes and won the 2019 legislative elections. Therefore, the objective of this study is to understand how the political marketing communication strategy used by Nasdem in East Nusa Tenggara Province, especially in the NTT electoral district I to win the 2019 legislative elections. The research used the concept of political parties, political campaigns, and political marketing communication using a qualitative approach and in-depth interview techniques. As a result, sales oriented political party marketing communication strategies used by Nasdem in the 2019 elections in the electoral district of East Nusa Tenggara Province I won the most votes. This strategy aims to get the number of votes from potential voters, and the representation of parties and personal figures that are 'sold' by political parties. Personal figures of the candidates have more impact for winning legislative elections than political party ideologies.